Novel roles of DC-SIGNR in colon cancer cell adhesion, migration, invasion, and liver metastasis. Issue 1 (December 2017) - Na, Heya; Liu, Xiaoli; Li, Xiaomeng; Zhang, Xinsheng; Wang, Yu; Wang, Zhaohui; Yuan, Menglang; Zhang, Yu; Ren, Shuangyi; Zuo, Yunfei
Abstract Background Tumor metastasis is an essential cause of the poor prognosis of colon cancer. DC-SIGNR is a C-type lectin that is frequently found on human liver sinusoidal endothelial cells. LSECtin, which is a homologue of DC-SIGNR, has been demonstrated to participate in colon cancer liver metastasis. Due to the similarities in the expression pattern and structure of the two proteins, we speculated that DC-SIGNR could also be involved in this process. Methods Colon cancer cells were treated with the DC-SIGNR protein or control IgG, after which cell migration, invasion, and morphology were assayed. Xenograft mouse models were used to determine the role of DC-SIGNR in colon cancer liver metastasis in vivo. In addition, a human gene expression array was used to detect differential gene expression in colon cancer cells stimulated with the DC-SIGNR protein. The serum level of DC-SIGNR was examined in colon cancer patients by ELISA, and the significance of DC-SIGNR was determined. Results In our research, we investigated whether DC-SIGNR promotes colon cancer cell adhesion, migration, and invasion. Knocking down mouse DC-SIGNR decreased the liver metastatic potency of colon cancer cells and increased survival time. Expressing human DC-SIGNR enhanced colon cancer liver metastasis. Furthermore, DC-SIGNR conferred metastatic capability on cancer cells by upregulating various metallothionein isoforms. To validate the above results, we also found that the serum DC-SIGNR level was statistically higher in colon cancer patients with liver metastasis compared with those without metastasis. Conclusions These results imply that DC-SIGNR may promote colon carcinoma hepatic metastasis and could serve as a promising therapeutic target for anticancer treatment.